Ethnobotany: A methods manual/ Gary J. Martin Etnobotánica: un manual de métodos - Martin, Gary J. (2004)
Ethnobotany, the study of the classification, use and management of plants by people, draws on a range of disciplines, including natural and social sciences, to show how conservation of plants and of local knowledge about them can be achieved. Ethnobotany is critical to the growing importance of developing new crops and products such as drugs from traditional plants. This book is the basic introduction to the field, showing how botany, anthropology, ecology, economics and linguistics are all employed in the techniques and methods involved. It explains data collection and hypothesis testing and provides practical ideas on fieldwork ethics and the application of results to conservation and community development. Case studies illustrate the explanations, demonstrating the importance of collaboration in achieving results.